The chart below contains the results of a survey in which students were asked about their cell phone plan.Cell Phones Plans
Plan
No cell phone
Voice only
Voice and texting
Voice, texting, and data
Students
20
14
12
4
What percent of the students surveyed have a phone plan with texting?

Answers

Answer 1
Answer:

Answer:

C - 32%

Step-by-step explanation:

Have a great day!

Answer 2
Answer:

Answer:

21324 and 3

Step-by-step explanation:


Related Questions

Simplify, picture attached
Find the perimeter of the figure
Joan works for 6 hr each weekday and 8 hr total on the weekends . She earns $6 an hr on weekdays and $9 an hour on weekends. How much money does she earn each week?
96 inches=_______feet?
Can you please give me 5 excersices to get perimeter and area, square or rectangle

0.48 as a fraction in simplest form

Answers

48/100 is the normal fraction but reduced it is 12/25 hope this helps hope i am brainliest i need one more 

Translate this sentence into an equation.
The product of Jenny's score and 6 is 72

Answers

Answer:

6x =72

Step-by-step explanation:

Let x = Jenny's score

Product means multiply, is means equals

x*6 = 72

6x =72

Answer:

6x =72

Step-by-step explanation:

HELP!!!!A hockey team scored 45 goals in its first 16 games.

At this rate, how many goals would the team score in an 80 game season?



A.
50


B.
109


C.
141


D.
225

Answers

First, find the unit rate. To do this, divide 45 ÷ 16 = 2.8125
The team scores 2.8125 goals per game (on average)
Now that you have the unit rate, you can find out how much they will score for any amount of games. Just multiply 2.8125 by 80 and you will get:

225 points in 80 games :)

An owner of a small store knows that in the last week 54 customers paid with cash, 42 paid with a debit card, and 153 paid with a credit card. Based on the number of customers from last week, which fraction is closest to the probability that the next customer will pay with cash?

Answers

Based on the number of customers from last week, the fraction is closest to the probability that the next customer will pay with cash is 54/249

How to get population mean?

Suppose population is wide and you cannot evaluate all the population at once. Then you do sampling of large enough size randomly. The mean of that sample will be then the estimate for the mean that population will pertain.

What is experimental probability?

Experimental probability calculates the probability of some event from the results of experiments.

For an event E, we get the experimental probability of that event

P_e(E) = \frac{\text{Number of times E occurred}}{\text{Number of times experiments was done}}

where, P_e(E) is denoting experimental probability of occurrence of E.

Here, the customers are not all known to us, they are population.

But we have some data of the previous customer. Taking them as the sample, we have:

Experimental probability of an event from sample = Predicted probability for that event in population.

For this case, from the previous data, we have:

  • 54 customers paid with cash
  • 42 customers paid with debit card
  • 153 customers paid with a credit card.

Total customers who paid = 153 + 42 + 54 = 249

Total customers who paid with cash = 54

Thus, if we take:

E = event that a customer pays with cash, then:

P_e(E) = (54)/(249)

This is the probability deduced from the previous data that the next customer will pay with cash.

Thus, based on the number of customers from last week, the fraction is closest to the probability that the next customer will pay with cash is 54/249

Learn more about probability here:

brainly.com/question/1210781

You would add 54+42+153=249 to find the total amount of customers from the previous week. Then you would divide 54/249= 0.2168 to find the amount of customers that used cash to total customers. The closest fraction would be about 1/5. 

100 POINTS HELP PLEASEEEE !!!HURRY!!!

Answers

                                           Question # 1 Solution

Answer:

(h-f)(-8)=-229

Step-by-step Solution:

Given

h(r)=-4r^(2)+4

f(r)=2r-7

As

(h-f)(r)=h(r)-f(r)

(h-f)(r)=-4r^(2)+4-(2r-7)

(h-f)(r)=-4r^(2)+4-2r+7)

We have to find (h-f)(-8)

So,

(h-f)(-8)=-4(-8)^(2)+4-2(-8)+7)

(h-f)(-8)=-4(64)+4+16+7

(h-f)(-8)=-4(64)+4+16+7

(h-f)(-8)=-256+4+16+7

(h-f)(-8)=-229

(h-f)(-8)=-229

                                             Question # 2 Solution

Answer:

(f.p)(9)=38979

Step-by-step Solution:

Given

f(s)=7s-2

p(s)=s^(3)-10s

As

(f.p)(s)=f(s).p(s)

(f.p)(s)=(7s-2)(s^(3)-10s)

(f.p)(s)=7s^4-2s^3-70s^2+20s

We have to find (f.p)(9)

So,

(f.p)(9)=7\left(9\right)^4-2\left(9\right)^3-70\left(9\right)^2+20\left(9\right)

(f.p)(9)=7\cdot \:9^4-2\cdot \:9^3-70\cdot \:9^2+20\cdot \:9

(f.p)(9)=9^4\cdot \:7-9^3\cdot \:2-9^2\cdot \:70+180

(f.p)(9)=45927-1458-5670+180

(f.p)(9)=38979

(f.p)(9)=38979

                                      Question # 3 Solution

Answer:

((f)/(p))(r)=(11r+8)/(r\left(r^2+6\right))

Step-by-step Solution:

Given

p(r)=r^(3)+6r

f(r)=11r+8

We have to find ((f)/(p))(r)

Using the formula

((f)/(p))(r)=(f(r))/(p(r))

As

p(r)=r^(3)+6r

f(r)=11r+8

So

((f)/(p))(r)=(11r+8)/(r^(3)+6r)

((f)/(p))(r)=(11r+8)/(r\left(r^2+6\right))

((f)/(p))(r)=(11r+8)/(r\left(r^2+6\right))

                                     Question # 4 Solution

Answer:

(h-p)(k)=5k^2-3-k^3-8k

Step-by-step Solution:

Given

h(k)=5k^(2)-3

p(k)=k^(3)+8k

We have to find (h-p)(k)

Using the formula

(h-p)(k)=h(k)-p(k)

As

h(k)=5k^(2)-3

p(k)=k^(3)+8k

So

(h-p)(k)=5k^(2)-3-(k^(3)+8k)

(h-p)(k)=5k^2-3-k^3-8k

(h-p)(k)=5k^2-3-k^3-8k

                                       Question # 5 Solution

Answer:

((p)/(g))(11)=(1287)/(155)

Step-by-step Solution:

Given

p(b)=b^(3)-4b

g(b)=b^(2)+4b-10

We have to find ((p)/(g))(11)

As

((p)/(g))(b)=(p(b))/(g(b))

((p)/(g))(b)=(b^(3)-4b)/(b^(2)+4b-10)

So

((p)/(g))(11)=(11^(3)-4(11))/(11^(2)+4(11)-10)

((p)/(g))(11)=(1287)/(155)

((p)/(g))(11)=(1287)/(155)

                                   Question # 6 Solution

Answer:

(f+g)(x)=x^2+20x-18

Step-by-step Solution:

Given

g(x)=x^(2)+11x-7

f(x)=9x-11

We have to find (f+g)(x)

As

(f+g)(x)=f(x)+g(x)

(f+g)(x)=9x-11+(x^(2)+11x-7)

(f+g)(x)=9x-11+x^(2)+11x-7

(f+g)(x)=x^2+20x-18

(f+g)(x)=x^2+20x-18

                                  Question # 7 Solution

Answer:

h(10)+g(10)=-983

Step-by-step Solution:

Given

h(w)=-11w^(2)-7

g(w)=w^(2)+3w-6

We have to find h(10)+g(10)

So,

h(10)=-11(10)^(2)-7

h(10)=-1107.....[1]

and

g(10)=10^(2)+3(10)-6

g(10)=124.....[2]

Adding Equation [1] and Equation [2]

h(10)+g(10)=-1107+124

h(10)+g(10)=-983

h(10)+g(10)=-983

                                   Question # 8 Solution

Answer:

(f+g)(-3)=-6

Step-by-step Solution:

Given

g(b)=b^(2)+9b+10

f(b)=3b+11

We have to find (f+g)(-3)

As

(f+g)(b)=f(b)+g(b)

So

(f+g)(b)=3b+11+b^(2)+9b+10

(f+g)(-3)=3(-3)+11+(-3)^(2)+9(-3)+10

(f+g)(-3)=-6

(f+g)(-3)=-6

                             

                                   Question # 9 Solution

Answer:

(f.h)(k)=33k^3+22k-12k^2-8

Step-by-step Solution:

Given

f(k)=-11k+4

h(k)=-3k^(2)-2

We have to find (f.h)(k)

As

(f.h)(k)=f(k).h(k)

So,

(f.h)(k)=(-11k+4).(-3k^(2)-2)

\mathrm{Apply\:FOIL\:method}:\quad \left(a+b\right)\left(c+d\right)=ac+ad+bc+bd

∵ FOIL means (First, Outer, Inner, Last)

(f.h)(k)=\left(-11k\right)\left(-3k^2\right)+\left(-11k\right)\left(-2\right)+4\left(-3k^2\right)+4\left(-2\right)

(f.h)(k)=33k^3+22k-12k^2-8

(f.h)(k)=33k^3+22k-12k^2-8

                                 Question # 10 Solution

Answer:

p(-8)-f(-8)=-581

Step-by-step Solution:

Given

p(s)=s^(3)+6s

f(s)=-2s+5

We have to find p(-8)-f(-8)

So,

p(-8)=(-8)^(3)+6(-8)

p(-8)=-560.....[1]

and

f(-8)=-2(-8)+5

f(-8)=21.....[2]

Subtracting Equation [2] from Equation [1]

p(-8)-f(-8)=-560-21

p(-8)-f(-8)=-581

p(-8)-f(-8)=-581

Keywords: function operation

Learn more about function operations from brainly.com/question/3725682

#learnwithBrainly

Answer:

-2229

Step-by-step explanation:

Which is greater 14/25 or 60%

Answers

Let us take the case of 14/25 first and get to the simplest form.
14/25 = 0.56
Now let us take the case of 60% and simplify
60% = 60/100
         = 6/10
         = 0.60
So we can clearly see from the above deduction that 60% is greater than 14/25. I hope the procedure for determining the greater number is clear for you to understand. You can always use this method for solving similar problems without requiring any help from outside.

Hey there!

“Which is greater 14/25 or 60%?”

14/25

= 14 ÷ 25

= 0.56

= 56%

56% is LESS than 60%

60% is GREATER than 56%

Therefore, your answer should be: [60% is BIGGER](THAN because 14/25 would give you the result of 56%)

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)